L. Tolstojus periodinėje lietuvių spaudoje (XIX a. pabaiga-XX a. I dešimtmetis) - Masionienė, Birutė (Literatūra, 1969)
L. N. Tolstoy’s influence upon the cultural life of Lithuania has not been properly studied though it is of great importance. In the article presented some light has been thrown upon the dissemination of L. N. Tolstoy’s ideas and his works in the period of 1894–1910. Tolstoy’s first critical commentaries in the period of press banning in Lithuania are very interesting. The democratic press of Lithuania called Tolstoy an enemy of the tsarist regime, an advocate of man’s rights; at the same time Tolstoy was an advocate of the Lithuanian people in its fight for its national rights. A special interest in Tolstoy’s personality and works arises in connection with the celebration of his 80th birthday anniversary (1908) as well as his death (1910). In the period under investigation the Lithuanian press differed greatly from the ideological point of view. Progressive, democratic, and reactionary-clerical trends are distinguished. Speaking about the dissemination of Tolstoy’s ideas and his works in Lithuania it is necessary to emphasize that a constant struggle between the two contradictory trends was going on in the pages of the Lithuanian press for their own interpretation of Tolstoy, using Tolstoy’s contradictory moral-philosophical system for the purposes of strengthening their ideological position. However, under rather complex circumstances of national oppression and slow formation of Lithuanian social democracy, in the progressive Lithuanian society and literary criticism a true interpretation of Tolstoy is formed.